GENE-16. CLINICALLY AGGRESSIVE MENINGIOMAS ARE CHARACTERIZED BY MUTATIONAL SIGNATURES ASSOCIATED WITH DEFECTIVE DNA REPAIR AND MUTATIONS IN CHROMATIN REMODELING GENES. (5th November 2018) - Kurz, Sylvia; Liechty, Benjamin; Kelly, Stephen; Vasudevaraja, Varshini; Bledea, Ramona; Wu, Peter; Serrano, Jonathan; Katz, Leah M; Silverman, Joshua; Pacione, Donato; Golfinos, John; Chi, Andrew; et al.
Abstract: BACKGROUND: Up to 20% of meningiomas are aggressive tumors with high recurrence rates and poor prognosis. Biomarkers predicting the risk of an unfavorable clinical course are lacking although aberrations in NF2, increased copy number variations and a hypomethylated phenotype have been associated with more aggressive behavior. Mutational signatures (MS) are characteristic patterns of somatic mutations seen in cancer genomes associated with aging, exposure to certain mutagens, or defective DNA repair. We aimed to identify MS patterns in clinically aggressive meningiomas. METHODS: We performed whole exome sequencing of 18 de novo meningiomas (locally invasive and recurrent WHO I, n=6; atypical WHO II, n=4; anaplastic WHO III, n=8). Median PFS was 18.9 months. Copy numbers and DNA methylation phenotype were assessed by DNA methylation array analysis. Mutational signatures were identified using published signature algorithms (COSMIC). RESULTS: MS1 and MS5 (aging) were found in 18 (100%) cases. MS associated with defective DNA MMR were highly prevalent: MS20 and MS26 were detected in 18 (100%) and MS6 in 2 (12%) cases. MS12 (unknown etiology) was present in 14 (82%) cases. Despite the association with defective DNA MMR, none (0%) of the MS6 cases harbored somatic mutations associated with DNA MMR while MS12 tumors were enriched for mutations in DNA MMR (43%), chromatin remodeling (36%) and other cancer-associated genes (7%). MS6 tumors had significantly lower indels compared to non-MS6 tumors (p=0.01). Tumors with mutations in chromatin remodeling genes had a significantly higher rate of single nucleotide variants (SNVs) compared to cases without such mutations (p=0.02). CONCLUSIONS: MS associated with defective DNA MMR were highly prevalent in this set of aggressive meningiomas. However, despite the association with DNA MMR, MS6 meningiomas harbored no somatic mutations associated with DNA MMR while MS12 tumors were enriched for mutations in DNA MMR, chromatin remodeling and cancer-associated genes.